Analisis Kebutuhan Tenaga Sterilisasi Berdasarkan Beban Kerja dengan Teknik Work Sampling Menggunakan Metode WISN di Unit CSSD di RS Bhayangkara Ruwa Jurai Bandar Lampung Tahun 2025 - Rossalia Artasya; Apri Sunadi; Eka Yoshida (Lembaga Pengembangan Kinerja Dosen, 2026)
The Central Sterile Supply Department (CSSD) is a crucial support unit in hospital service quality, particularly in ensuring the availability of sterile medical instruments. An imbalance between workload and personnel capacity may result in delays, increased risk of infection, and reduced efficiency. This study aimed to analyze the staffing needs of the sterilization unit at Bhayangkara Hospital Level III Lampung in 2025 using a managerial and evidence-based approach. This study employed a descriptive quantitative design using the Workload Indicators of Staffing Need (WISN) method. Data were obtained from direct observations, document reviews, and interviews, and analyzed according to workload standards set by the Ministry of Health. The findings showed that the sterilization unit had 5 available staff, while the analysis indicated a requirement of 5-6 staff members. Factors contributing to the shortage included increasing demand for surgical procedures, limited shifts, and insufficient distribution of tasks. This study recommends the addition of at least 1 sterilization staff to achieve optimal service standards, along with periodic training and workload-based scheduling. Strengthening human resources in the CSSD is essential to improve efficiency, ensure patient safety, and support the overall quality of hospital services.